Acetyl-11-Keto-β-Boswellic Acid Promotes Osteoblast Differentiation by Inhibiting Tumor Necrosis Factor-α and Nuclear Factor-κB Activity. Issue 7 (October 2018) - Bai, Fan; Chen, Xuewu; Yang, Hui; Xu, Hong-Guang
Abstract : Abstract: Tumor necrosis factor (TNF) -α plays a crucial role in rheumatoid arthritis (RA)-related bone loss disease. The main mechanism of action of RA induced bone loss is the significant inhibitory effect of TNF-α on osteoblast differentiation. TNF-α inhibits osteoblast differentiation mainly by activating nuclear factor (NF) -κB signaling pathway. Owing to the crucial role of TNF-α and NF-κB in the inhibition of osteoblast differentiation, they are considered as targets for the development of therapeutic drugs. In the present study, we evaluated the NF-κB inhibitor Boswellic acid (BA) and its derivatives in the regulation of osteoblast differentiation and the molecular mechanism. Based on the cell model of TNF-α induced inhibition of osteoblast differentiation of MC3T3-E1, the regulatory role of BAs was studied. The result of MTT assay indicated that bone morphogenetic protein (BMP) -2, TNF-α, or acetyl-11-keto-β-BA (AKBA) impact no significant effect for cell viability of MC3T3-E1. The results of alkaline phosphatase (ALP activity assay and real-time polymerase chain reaction indicated that AKBA blocked TNF-α-induced inhibition of the expression of osteoblast markers, suggesting that AKBA rescued osteoblast differentiation from TNF-α-induced inhibition. Additionally, AKBA stimulated the BMP-2-induced expression of osteoblast markers, suggesting that AKBA promotes osteoblast differentiation directly. The results of western blotting and luciferase assay indicated that N-κB signaling was activated by TNF-α. The overexpression of NF-κB component p65 in MC3T3-E1 was found to attenuate the positive effect of AKBA in osteoblast differentiation, suggesting that AKBA potentiates osteoblast differentiation by inhibiting NF-κB signaling. Collectively, AKBA promotes osteoblast differentiation by inhibiting TNF-α and NF-κB. Our study revealed a new discovery of AKBA in regulating osteoblast differentiation, and demonstrated that AKBA may be a potential anabolic agent in the treatment of RA-derived bone loss disease.